Live-attenuated pediatric parainfluenza vaccine expressing 6P-stabilized SARS-CoV-2 spike protein is protective against SARS-CoV-2 variants in hamsters - Liu, Xueqiao; Park, Hong-Su; Matsuoka, Yumiko; Santos, Celia; Yang, Lijuan; Luongo, Cindy; Moore, Ian N.; Johnson, Reed F.; Garza, Nicole L.; Zhang, Peng; Lusso, Paolo; Best, Sonja M.; et al. (PLoS pathogens, 2023)
The pediatric live-attenuated bovine/human parainfluenza virus type 3 (B/HPIV3)-vectored vaccine expressing the prefusion-stabilized SARS-CoV-2 spike (S) protein (B/HPIV3/S-2P) was previously evaluated in vitro and in hamsters. To improve its immunogenicity, we generated B/HPIV3/S-6P, expressing S further stabilized with 6 proline mutations (S-6P). Intranasal immunization of hamsters with B/HPIV3/S-6P reproducibly elicited significantly higher serum anti-S IgA/IgG titers than B/HPIV3/S-2P; hamster sera efficiently neutralized variants of concern (VoCs), including Omicron variants. B/HPIV3/S-2P and B/HPIV3/S-6P immunization protected hamsters against weight loss and lung inflammation following SARS-CoV-2 challenge with the vaccine-matched strain WA1/2020 or VoCs B.1.1.7/Alpha or B.1.351/Beta and induced near-sterilizing immunity. Three weeks post-challenge, B/HPIV3/S-2P- and B/HPIV3/S-6P-immunized hamsters exhibited a robust anamnestic serum antibody response with increased neutralizing potency to VoCs, including Omicron sublineages. B/HPIV3/S-6P primed for stronger anamnestic antibody responses after challenge with WA1/2020 than B/HPIV3/S-2P. B/HPIV3/S-6P will be evaluated as an intranasal vaccine to protect infants against both HPIV3 and SARS-CoV-2.